2016
DOI: 10.1186/s40064-016-3133-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eating habits and lifestyle in patients with obesity before and after bariatric surgery: a single Italian center experience

Abstract: BackgroundThe study evaluated and compared the eating habits and lifestyle of patients with moderate to severe obesity who have undergone Roux-en-Y Gastric Bypass (RYGB) and Sleeve Gastrectomy (SG).MethodsFood frequency (FF), food habits (FH), physical activity and life style (PA) as well as smoking habits (SH) were analyzed in 50 RYGB (25 M; aged: 24–64) and 50 SG patients (25 M; aged: 22–63) by means of a validated questionnaire, before (T0) and 6 months (T1) post bariatric surgery. A score for each section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
8
0
4
Order By: Relevance
“…We also found that the regainers had a decreased fiber intake characterized by the complete elimination of fruits and vegetables from the daily diet along with low intake of water (Table 2). These findings illustrate that weight regain is more due to poor selection of healthy foods rather than excessive consumption, and thus, it is mainly attributed to food quality rather than quantity [16].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the regainers had a decreased fiber intake characterized by the complete elimination of fruits and vegetables from the daily diet along with low intake of water (Table 2). These findings illustrate that weight regain is more due to poor selection of healthy foods rather than excessive consumption, and thus, it is mainly attributed to food quality rather than quantity [16].…”
Section: Discussionmentioning
confidence: 99%
“…Sendo as causas da obesidade multifactoriais, é necessária uma equipa multidisciplinar para as avaliar no pré-operatório e contribuir para o seu tratamento em todo o processo. 8,17,30 Esta deve reunir periodicamente, discutindo os casos e elaborando planos de ação individuais, centrados no doente e na melhor forma de o tratar, devendo procurar-se consenso quanto à indicação (ou não) do doente para cirurgia e registando os vários pareceres no processo clínico. 14 Cabe ao coordenador da equipa, a avaliação do impacto da obesidade no estado de saúde global e a análise das respostas terapêuticas disponíveis em articulação estreita com os restantes profissionais.…”
Section: Equipa Multidisciplinarunclassified
“…Jika wanita memiliki lemak tubuh melebihi dari 30%, maka dianggap mengalami obesitas, sedangkan laki-laki ditetapkan ambang batas 25%. Secara umum, apabila mempunyai berat badan 20% lebih tinggi dari nilai tengah kisaran berat badannya yang normal maka seseorang tersebut mengalami kejadian obesitas (8).…”
Section: Pembahasanunclassified